Pengaruh Lingkungan Kerja Nonfisik dan Pengembangan Karier terhadap Kepuasan Kerja dengan Komitmen Afektif sebagai Variabel Mediasi pada Karyawan Pemasar Kredit PT Bank Negara Indonesia (Persero) Regional Palembang - M Riko Ade Putra; Wita Farla; Muhammad Ichsan Hadjri (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the effects of the non-physical work environment and career development on job satisfaction, with affective commitment as a mediator, among 131 credit marketing employees at PT Bank Negara Indonesia (Persero) Regional Palembang. Using a quantitative cross-sectional design and census sampling, data were analyzed using PLS-SEM. Results show that the non-physical work environment and career development positively and significantly affect job satisfaction and affective commitment. Affective commitment also positively and significantly affects job satisfaction but does not significantly mediate either relationship. These findings show that supportive interpersonal conditions and transparent career development directly strengthen employee job satisfaction. Keywords: Non-Physical Work Environment; Career Development; Affective Commitment; Job Satisfaction; Banking Industry